Effect of supplementation with Glycyrrhiza uralensis extract and Lactobacillus acidophilus on growth performance and intestinal health in broiler chickens - Li, Ximei; Li, Jiawei; Yuan, Haotian; Chen, Yan; Li, Shuaibing; Jiang, Susu; Zha Xi, Yingpai; Zhang, Guohua; Lu, Jianxiong (Frontiers in Veterinary Science, 2024)
Four hundred twenty 1-day-old male Liangfenghua broiler chickens were randomly assigned to four groups to investigate the effect of dietary Glycyrrhiza uralensis extract (GUE), Lactobacillus acidophilus (Lac) and their combination (GL) on growth performance and intestinal health in broilers in an 84-day feeding experiment. Supplementary 0.1% GUE and 4.5×10 7 CFU/g Lac significantly increased average daily gain (ADG), and GL (0.1% GUE and 4.5×10 7 CFU/g Lac) increased ADG and average daily feed intake (ADFI), and decreased feed conversion rate (FCR) in broilers aged 29 to 84 d and 1 to 84 d. Dietary GUE, Lac and GL increased the superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) activity and decreased Malondialdehyde (MDA) content in the jejunum mucosa of broilers, and increased secretory IgA (sIgA) content in broilers at 84 d. Moreover, GUE, Lac and GL increased cecal microbial richness and diversity, and modulated microbial community composition. Both GUE and Lac reduced the harmful bacteria Epsilonbacteraeota, Helicobacter, and H. pullorum at 28 d and Proteobacteria, Escherichia, and E. coli at 84 d, while Lac and GL increased beneficial bacteria Lactobacillus and L. gallinarum at 28 d. Compared with individual supplementation, GL markedly increased the SOD activity and the sIgA content, and reduced Helicobacter and Helicobacter pullorum. In conclusion, GUE and Lactobacillus acidophilus as feed additives benefit growth performance and intestinal health, and their combined use shows an even more positive effect in broilers.